Etnis Tionghoa di Indonesia : kumpulan tulisan - Tan, Mely G. (Jakarta : Yayasan Obor Indonesia, 2008)
Ethnic Chinese in Indonesia; collected articles
Includes bibliographical references
In English, and three articles in Indonesian
Keywords: Chinese -- Indonesia